Repeatability and genetic advances in early maturing maize hybrid trials conducted under Striga-infested and non-infested conditions - Abubakar, A.M.; Adejumobi, I.I.; Fowobaje, K.R.; Dieng, I.; Saminu, Z.; Imoro, S.; Badu-Apraku, B. (2025)
In sub-Saharan Africa (SSA), maize (Zea mays L.) is both a cash crop and an important staple crop. However, Striga hermonthica infection constrains its production and productivity. A total of 159 hybrids from 21 international trials were evaluated under Striga-infested (STRINF) and Striga non-infested (STRNON) conditions at Mokwa and Abuja, Nigeria, from 2010 to 2021. The data were used to (i) determine the genetic enhancements in grain yield and Striga adaptive traits and (ii) assess the repeatability of the trials in identification of promising hybrids. Significant annual genetic gains in grain yield of 3.40% and 3.71% with increases of 76.87 and 127.02 kg ha − 1 yr − 1 were recorded under STRINF and STRNON conditions, respectively. The genetic gains in grain yield were associated with 3.04 and 2.25% decreases in Striga damage ratings at 8 and 10 weeks after planting (WAP), respectively, and 1.27% in the number of emerged Striga plants at 10 WAP. The results indicated that ears per plant and flowering dates had the highest consistency in repeatability estimates while the number of emerged Striga plants at 8 and 10 WAP recorded the lowest consistency in repeatability estimates. Generally, substantial progress has been achieved with a good level of repeatability estimates for the early maturing maize hybrid trials evaluated under STRINF and STRNON conditions.Those results have demonstrated that the breeding strategies adopted during the 12-year breeding period have been effective, and that the potential of the trials in the exploration of the genetic potential of the hybrids for commercialization in the SSA for food security and poverty alleviation.